Reversible photo-control over transmembrane anion transport using visible-light responsive supramolecular carriers - Kerckhoffs, A; Langton, MJ (Royal Society of Chemistry, 2020)
Ion transport across lipid bilayer membranes in biology is controlled by membrane proteins, which in turn are regulated in response to chemical-, physical- and photo-stimuli. The design of synthetic supramolecular ion transporters able to be precisely controlled by external signals, in particular bio-compatible wavelengths of visible light, is key for achieving spatio-temporal control over function. Here we report two-colour responsive molecular photo-switches that act as supramolecular transmembrane anion carriers. Reversible switching of the photo-switch within the lipid bilayer membrane is achieved using biocompatible visible wavelengths of light, such that temporal control over transmembrane anion transport is achieved through alternating irradiation with red and blue light.